2017
DOI: 10.1002/cncr.30720
|View full text |Cite
|
Sign up to set email alerts
|

The Breast and Cervical Cancer Early Detection Program, Medicaid, and breast cancer outcomes among Ohio's underserved women

Abstract: Medicaid/peridiagnosis women are at particularly high risk to be diagnosed with advanced-stage disease. Efforts to reduce breast cancer disparities must target this group of women before they present to Medicaid. Cancer 2017;123:3097-106. © 2017 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(33 citation statements)
references
References 42 publications
0
33
0
Order By: Relevance
“…Previous studies have shown that prediagnosis enrollees have more favorable cancer survival outcomes compared with peridiagnosis/postdiagnosis enrollees, perhaps reflecting the better access to care for prediagnosis enrollees. 40,41 In addition, prediagnosis enrollees may be more likely to present for care in the face of early cancer symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that prediagnosis enrollees have more favorable cancer survival outcomes compared with peridiagnosis/postdiagnosis enrollees, perhaps reflecting the better access to care for prediagnosis enrollees. 40,41 In addition, prediagnosis enrollees may be more likely to present for care in the face of early cancer symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 13 studies that examined coverage disruptions and stage of disease at diagnosis, details for study populations, settings, measures of coverage disruptions and outcomes, comparison groups, and key findings are listed in Table 3 (33,34,40,41,(43)(44)(45)(46)(47)(48)(49)(50)(51). Each of these studies examined timing of Medicaid enrollment in a single state, including California, Michigan, New Jersey, North Carolina, Ohio, or Washington.…”
Section: Stage Of Disease At Diagnosismentioning
confidence: 99%
“…In addition, the linked data set benefits cancer registries by identifying potentially missed cancer cases and providing missing race data. For example, studies have been performed using the data set to compare stage of disease at the time of diagnosis with screening histories among women with cancer …”
Section: Cancer Control Programsmentioning
confidence: 99%
“…For example, studies have been performed using the data set to compare stage of disease at the time of diagnosis with screening histories among women with cancer. [34][35][36]…”
Section: National Breast and Cervical Cancer Early Detection Programmentioning
confidence: 99%